Study Of Multi-Walled Carbon Nanotube Effect On Polyvinyl Alcohol With Calcined Cuttlebone - Foo, Tsi Yin (2020)
The present study demonstrates the effects of multi-walled carbon nanotube (MWCNT) on polyvinyl alcohol (PVOH) with calcined cuttlebone. The aims of this study are to determine the mechanical, thermal and chemical properties as well as the morphology of MWCNT added with calcined cuttlebone in PVOH matrix. Since PVOH presents some drawbacks in bone scaffolding applications, MWCNT and calcined cuttlebone were used as reinforcing material in this study. Three compounds (PVOH-MWCNT-calcined cuttlebone) were blended together, cast and analysed. The loading of MWCNT incorporated was varied from 1 phr to 3 phr with 2 phr and 5 phr of calcined cuttlebone whereas the loading of PVOH was fixed at 100 phr. Characterization tests were made according to their mechanical properties, morphologies, interaction of bonding, crystallinity and thermal properties. Mechanical properties were observed to increase with increasing MWCNT loading in which the maximum tensile strength is 42.65 MPa for 2 phr calcined cuttlebone and 41.43 MPa for 5 phr calcined cuttlebone. Scanning electron microscopy (SEM) images suggested that agglomeration of MWCNT in PVOH matrix tends to occur at high loading (5phr) of calcined cuttlebone and well distribution was induced with increasing loading of MWCNT. X-ray diffraction (XRD) results showed that PVOH peaks were observed at the range of 19o -21o and crystallinity of PVOH/MWCNT composite is the highest at low (2phr) amount of calcined cuttlebone. Fourier transform infrared spectroscopy (FTIR) analysis showed that the interaction of bonding between molecules increased with increasing loading of MWCNT at low (2 phr) loading of calcined cuttlebone. Differential scanning calorimetry (DSC) results showed that the melting temperature increased with increasing loading of MWCNT at both 2 phr and 5 phr calcined cuttlebone. The highest enthalpy of melting is 44.46 J/g and 38.64 J/g at both 2 phr and 5 phr calcined cuttlebone respectively. In short, the mechanical and thermal properties increased with increasing loading of MWCNT but the matrix tends to agglomerate when minimum calcined cuttlebone content is exceeded whereas the addition of 2 phr calcined cuttlebone induced the strongest interaction of bonding between molecules.